Enhance Effectiveness of Moringa Leaves with Staphylococcus Epidermidis Bacteria - Ali Napiah Nasution (Budapest International Research and Critics University, 2021)
Plants are a source of various types of medicinal chemical compounds, one of which is as an anti-infection where the use of natural plant-based ingredients (herbs) is again a trend among Indonesians. Cleanliness is very important because of the increasing number of diseases that arise due to bacteria and germs. The skin is the part that covers the surface of the body and has the main function of protecting it from various kinds of disturbances and external stimuli. Moringa leaves are natural ingredients that have antibacterial potential. Moringa (Moringa oleifera, Lamk) is a plant that has antibacterial benefits. Staphylococcus Epidermidis is a bacterium that causes various pyogenic and skin infections, separation, abscess formation, and fatal septicemia. This study aims to test the antibacterial activity of Moringa leaves against Staphylococcus Epidermidis. The method used in the extraction of Moringa leaves is maceration using ethanol as a solvent. As for testing, it is known that the moringa leaf extract has antibacterial activity against Staphylococcus Epidermidis at concentrations of 5%, 10%, 20%, 40%, and 80% and the minimum inhibitory content (MIC) is 12 mm in Staphylococcus Epidermidis. The difference in the concentration of Moringa leaf extract influenced the inhibition of the growth of Staphylococcus Epidermidis bacteria.